Chemical speciation of heavy metals in bioaugmented and non- bioaugmented soils from Taman Beringin landfill - Umm-kulthum Gimba; Sharifah Mohammad; Fauziah Shahul Hamid (Hasanuddin University, 2021)
Heavy metal pollution has led to serious consequences since the dawn of industrialization. The aim of this study is to compare the speciation of heavy metals in bioaugmented and non-bioaugmented soils from Taman Beringin landfill, Malaysia. This is to allow the proper understanding of the specific forms of heavy metals and their mobility in the environment. Sequential extraction process based on Tessier et al. (1979), Tsang et al (2007) and standard ISO 11466 (1995) was performed for the determination of eight heavy metals (Cr, Mn, Co, Ni, Cu, Zn, Cd and Pb) in soils samples. The results revealed that the percentage reduction of the mobile and non mobile forms (F1, F2, F3, F4 and F5) of heavy metals varied for all metals in non- bioaugmented and bioaugmented soils. Additionally, the distribution of the specific form of the metals ( for Mn, Co, Ni, Cu and Pb) changed after bioaugmentation at Day 100.